Shear viscosity of a pion gas due to ?pp and spp interactions - Ghosh, Sabyasachi [UNESP]; Krein, Gastão [UNESP]; Sarkar, Sourav (My University, 2015)
We have calculated the shear viscosity of a medium containing pions where the propagating pion has a finite thermal width due to interaction with the low mass resonances, s and ?. With the help of standard thermal field theoretical technique, the thermal width of the pion has been calculated from the pion self-energy diagram for ps and p? loops, where an effective Lagrangian density has been used for interaction part. We have found a very small value of shear viscosity by entropy density ratio (?/s), which is very close to the KSS bound.